Formulation Of Antifungal Solid Soap From 96% Ethanol Extract Of Neem Leaves (Azadirachta Indica A.Juss) Against Malassezia Furfur ATCC 14251 - Diyah Nurayuni; Anna Fitriawati; Annie Rahmatillah (CV. AFDIFAL MAJU BERKAH, 2026)
Fungal skin infections are still a health problem in tropical regions, especially those caused by Malassezia furfur, so alternative natural skin cleansing preparations are needed that are safe and effective. Neem leaves (Azadirachta indica A. Juss) are known to have antifungal activity and have the potential to be developed into solid soap preparations. This study aims to formulate an antifungal solid soap made from 96 percent ethanol extract of neem leaves, evaluate the physical quality of the preparation, and test its antifungal activity against Malassezia furfur. This study is a laboratory experimental study with a pretest-posttest only control group design. The study population was neem leaves obtained from Mount Pati District, Semarang, with simplicia samples selected using a purposive sampling technique. The research instruments included formulation equipment, physical quality tests based on SNI 3532:2016, and antifungal activity tests using the well diffusion method, while data analysis was carried out using nonparametric statistical tests. The results showed that all soap formulas met the physical quality requirements, and the formulation with a 10 percent extract concentration produced the largest inhibition zone diameter against Malassezia furfur, although it was still relatively weak. The conclusion of this study is that neem leaf extract solid soap has potential as a natural skin cleanser with antifungal activity, but further development and optimization of the formulation are needed to increase its effectiveness.